STAT3 Cooperates With Phospholipid Scramblase 2 to Suppress Type I Interferon Response - Tsai, Ming-Hsun; Lee, Chien-Kuo (Frontiers in Immunology, 2018)
Type I interferon (IFN-I) is a pluripotent cytokine that modulates innate and adaptive immunity. We have previously shown that STAT3 suppresses IFN-I response in a manner dependent on its N-terminal domain (NTD), but independent of its DNA-binding and transactivation ability. Using the yeast two-hybrid system, we have identified phospholipid scramblase 2 (PLSCR2) as a STAT3 NTD binding partner and a suppressor of IFN-I response. Overexpression of PLSCR2 attenuates ISRE-driven reporter activity, which is further aggravated by co-expression of STAT3. Moreover, PLSCR2 deficiency enhances IFN-I-induced gene expression and antiviral activity without affecting the activation or nuclear translocation of STAT1 and STAT2 or the assembly of ISGF3 complex. Instead, PLSCR2 impedes promoter occupancy by ISGF3, an effect further intensified by the presence of STAT3. Moreover, palmitoylation of PLSCR2 is required for its binding to STAT3 and for this suppressive activity. In addition to STAT3, PLSCR2 also interacts with STAT2, which facilitates the suppressive effect on ISGF3-mediated transcriptional activity. Together, these results define the role of a novel STAT3-PLSCR2 axis in fine-tuning IFN-I response.